Socialization of Post-COVID-19 Community Economic Strengthening Strategy and Regional Poverty Alleviation Strategy in Aceh Besar Regency - Mukhlis, Mukhlis; Sakir, A; Darwanis, Darwanis; Jamal, Abd; Nisva, Raisa Ullya; Dawood, Taufiq C; Umuri, Khairil; Sari, Meutia Dwi Novita; Nabilah, Nabilah; Zikran, Ghrina (Jurnal Pengabdian Bakti Akademisi, 2024)
This community service activity aimed to address the economic challenges faced by the people of Aceh Besar post-COVID-19 and to develop effective poverty alleviation strategies for the region. Conducted on February 14, 2023, at the Dekranasda Aceh Besar office, this initiative was a collaboration between the Management Department, Faculty of Economics and Business, Universitas Syiah Kuala, and the Government of Aceh Besar. The primary objectives were to enhance the understanding and skills of local stakeholders in formulating and implementing economic strengthening strategies and to foster collaboration among various community elements. The service-learning method was employed, integrating academic learning with community service to provide practical solutions to real-world problems. The activity involved 150 participants, including members of the Aceh Besar Regional House of Representatives (DPRK), 58 regional government organizations (OPD), Aceh's Development Planning Agency (Bappeda), the Head of Aceh Besar Statistics Bureau (BPS), representatives from NGOs, community leaders, local officials, academics, and other relevant stakeholders. The activities included presentations, workshops, and group discussions led by experts from Universitas Syiah Kuala and Bappeda Aceh. The results showed a significant increase in participants' understanding and skills, with 85% reporting improved knowledge in economic strengthening strategies. Additionally, eight concrete action plans were developed and implemented by the participants in their respective communities. The activity's success is evident from the high levels of participation and positive feedback, demonstrating its effectiveness in achieving its objectives. These outcomes contribute to the Sustainable Development Goals (SDGs), particularly in poverty alleviation and economic well-being. Despite minor challenges such as time constraints and resource limitations, the activity successfully fostered collaboration and provided valuable insights for future community service initiatives.